JAMBI: AN UNKNOWN PLACE OR LOST MEMORY IN OTTOMAN POLITICAL MIND? - Ã–zay, Mehmet (Journal of Al-Tamaddun, 2019)
The period commencing from 1850s onwards witnessed drastic changes caused by internal and external factors both in the Ottoman state and the Sultanate of Jambi, a Malay political entity in the eastern part of Sumatra Island. Furthermore, the latter’s demands of political recognition and collaboration failed to see signifiant fruit as reflected by the entrenching colonial invasion, while on the other hand, the Ottoman decline contributed to the failure of relevant recognition of Jambi’s sovereignity and geographical reality. This paper analyses Ottoman conception of the geographical identification and definition of, in particular, Jambi and in general northern and eastern Sumatra Island in the second part of the 19th century. And it seeks some insight to elaborate some documents talking about a political issue between the Ottoman State and the Sultanate of Jambi. The striking point is that though the regional polities had earlier corresponded with the Ottoman court, the officials of the latter referred inconsistently to some particular places in Sumatra Island in the documents with names distinct from each other. The question is whether the Ottoman political mind devoted time and energy to critically examine the authenticity of the mentioned documents. Based on the relevant archival documents, the paper comparatively examines the geographical references distinctively mentioned in correspondences in both Arabic texts and translated forms in the Ottoman language. The confusing geographical definitions can be observed as a reflection of how the Ottoman beaureucracy unsustainably handled diplomatic issues which might have potentially been misleading representations of Malay geography. Relying on correspondences between the Sultanate of Jambi and the Ottoman State, for a period of 40 years commencing from 1860s to 1903, kept in the Ottoman archive, it is expected that this paper will draw attention, though an alternative view point on the Ottoman bureaucratic knowledge on Islamic geography in the Island of Sumatra.